Calculating rutting of some thin flexible pavements from repeated load triaxial test data - Qiao, Yaning; Dawson, Andrew; Huvstig, Anders; Korkiala-Tanttu, Leena (Taylor & Francis, 2015)
This paper describes parts of a Nordic pavement performance prediction model study (at the project level of the NordFoU project) where a material performance model, developed at VTT research centre in Finland, has been selected as a mean of calculating the permanently accumulated (plastic) deformation (i.e. rutting) of unbound granular materials (UGMs) in flexible pavements subjected to trafficking. The paper aims to assess the suitability of this VTT model application to Swedish roads comprising thin asphalt layers over a thick UGM base. To achieve this, the VTT model has been used to calculate the deformations of two tested road sections in Sweden. These calculations have been compared with another permanent deformation model for UGM (the Gidel model) and with rutting measurements from trafficked pavements. It is shown from this study that the applied rutting prediction method with VTT model is capable of predicting the development of rutting depth despite some overestimations.